2019
DOI: 10.1002/jcla.22979
|View full text |Cite
|
Sign up to set email alerts
|

Integrin α7 high expression correlates with deteriorative tumor features and worse overall survival, and its knockdown inhibits cell proliferation and invasion but increases apoptosis in breast cancer

Abstract: Background This study aimed to investigate the correlation of integrin α7 (ITGA7) expression with clinical/pathological characteristics and overall survival (OS), and its knockdown on inhibiting cell activities in breast cancer. Methods A total of 191 breast cancer patients underwent surgery were retrospectively reviewed, and ITGA7 expression in tumor tissues was determined by immunofluorescence and real‐time quantitative polymerase chain reaction. Patients’ clinical/pathological data were recorded, and OS was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Another recent report provides strong in vitro and in vivo evidence that ITGA7 interacts with laminin‐induced outside‐in signaling to participant in the growth and invasion of glioblastoma stem‐like cells . Meanwhile, an interesting in vitro experiment reveals that ITGA7 knockdown reduces cell proliferation and cell invasion, while enhances cell apoptosis rate in breast cancer cells . Additionally, a previous study highlights a surprising function of ITGA7 as a tumor promoter in OSCC malignancy that ITGA7 not only upregulates stemness‐associated genes expressions (such as octamer‐binding transcription factor 4 [OCT4], SRY [sex‐determining region Y]‐box 2 [SOX2], Nanog homeobox [NANOG] and CD90), but also enhances abilities to self‐renew of OSCC cells via activating the FAK‐mediated signaling pathways .…”
Section: Discussionmentioning
confidence: 99%
“…Another recent report provides strong in vitro and in vivo evidence that ITGA7 interacts with laminin‐induced outside‐in signaling to participant in the growth and invasion of glioblastoma stem‐like cells . Meanwhile, an interesting in vitro experiment reveals that ITGA7 knockdown reduces cell proliferation and cell invasion, while enhances cell apoptosis rate in breast cancer cells . Additionally, a previous study highlights a surprising function of ITGA7 as a tumor promoter in OSCC malignancy that ITGA7 not only upregulates stemness‐associated genes expressions (such as octamer‐binding transcription factor 4 [OCT4], SRY [sex‐determining region Y]‐box 2 [SOX2], Nanog homeobox [NANOG] and CD90), but also enhances abilities to self‐renew of OSCC cells via activating the FAK‐mediated signaling pathways .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that ITGA7 is involved in the pathological progression of different carcinomas through affecting cell activities such as cell migration and invasion (5,6,9,(13)(14)(15). For example, the interaction between ITGA7 and laminin-induced outside-in signaling contributed to glioblastoma stem-like cell growth and invasion (12).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, ITGA7 promoted the stemness of OSCC cells via FAK/MAPK/ERK signaling, which subsequently induced the tumorigenicity and metastasis of OSCC (5). In addition, ITGB7 knockdown enhanced cell apoptosis but inhibited cell proliferation and invasion in breast cancer (14). Although a few studies have been performed to explore the role of ITGA7 in different types of carcinoma, there remain certain contradictions.…”
Section: Discussionmentioning
confidence: 99%
“…A high expression of COL5A2 is associated with metastasis in renal cell carcinoma [88]. ITGA7 upregulation promotes the proliferation and invasion of breast cancer cells [89].…”
Section: Discussionmentioning
confidence: 99%